2000
DOI: 10.2190/v98r-5etx-w9ly-wd3j
|View full text |Cite
|
Sign up to set email alerts
|

Examining the “Male, Antisocial” Stereotype of High Computer Users

Abstract: The popular stereotype of the frequent computer user persists to be one of a male, socially inadequate and isolated individual-a perception which has been found to cause many students to avoid coming into contact with information and communications technology (ICT), both inside and outside of school. This article reports on a study examining the gender and social competency of both frequent and infrequent computer-using students in Year 12 (n = 117). The results suggest that students who are highly oriented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 25 publications
1
39
1
3
Order By: Relevance
“…However, both the Weinberger and the Blum and Frieze studies considered college age students. Only Schott and Selwyn (2000) looked at high school age girls. This research explored the male-dominated, geek and loner stereotype in the United Kingdom.…”
Section: Challenging the Geek Stereotypementioning
confidence: 99%
See 1 more Smart Citation
“…However, both the Weinberger and the Blum and Frieze studies considered college age students. Only Schott and Selwyn (2000) looked at high school age girls. This research explored the male-dominated, geek and loner stereotype in the United Kingdom.…”
Section: Challenging the Geek Stereotypementioning
confidence: 99%
“…Given that significant efforts are being made to combat the geek and loner image among young women, and that the Schott and Selwyn (2000) study at least suggested the possibility that this misconception might be diminishing, the current study was designed to ferret out the truth. It is the first study to specifically address this question with a large number of urban high school girls in the United States.…”
Section: The Purpose Of This Studymentioning
confidence: 99%
“…Recent studies of how people learn to use computers from the social developmental perspective concern various issues. These issues can be grouped into the following categories: (1) Internet addiction (Davis, Smith, Rodrigue, and Pulvers, 1999;Griffiths, 1997;Young, 1996), (2) social identity and personality (Turkle, 1984(Turkle, , 1995Ike, 1997), gender difference and stereotype (Rocheleau, 1995;Schott and Selwyn, 2000), (3) computer anxiety and phobia , (4) social interaction and socialization (Crook, 1992;Freeman and Somerindyke, 2001;Lawhorn, Ennis, and Lawhorn, 1996;McKenna, 1999), and (5) life intrusion, privacy, and on-line predators (U. S.…”
Section: Human Development and Learning To Use Computersmentioning
confidence: 99%
“…Because the computer science prototype is perceived as incongruent with the female gender role (Cheryan et al 2009; Diekman et al in press; Margolis and Fisher 2002; Schott and Selwyn 2000), we hypothesize that women will perceive less similarity between themselves and computer scientists than men will perceive. Such perceptions of STEM fields may be inaccurate (Beyer 1999a; Borg 1999), but that does not preclude their influence (Cheryan et al 2009).…”
Section: Introductionmentioning
confidence: 96%